2011
DOI: 10.2174/1874918601104010001
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Mortality in Nigeria: Do Place of Delivery and Delivery Assistants Matter?

Abstract: Abstract:Background: Studies in developed countries have shown that deliveries which occur at home and under the supervision of unskilled attendants present a high risk of perinatal death. However, it is unclear, especially in sub-Saharan Africa (SSA) where studies are limited, on precisely how these factors may influence perinatal mortality. This is particularly of interest considering that majority of births in SSA occur at home under the supervision of unskilled attendants and perinatal mortality in the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…This finding is consistent with previous studies [40,41], which attributed this finding to limited access to health facilities and maternal healthcare services, such as delivery assisted by a healthcare professional, and prenatal and postnatal care. This disproportionally hinders rural dwellers from receiving adequate healthcare services, resulting in a high probability of neonatal death.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies [40,41], which attributed this finding to limited access to health facilities and maternal healthcare services, such as delivery assisted by a healthcare professional, and prenatal and postnatal care. This disproportionally hinders rural dwellers from receiving adequate healthcare services, resulting in a high probability of neonatal death.…”
Section: Discussionsupporting
confidence: 93%
“…However, the odds revealed higher likelihood of U5M among home deliveries. This nding was in agreement with other studies done in the developing countries of Nigeria and South Africa [40,41]. However, other studies have revealed a lower probability of child's death among deliveries that occurs in health facilities as compared to home deliveries [10,21,23].…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, such accessibility has been complicated by the emergence of motorbikes, which appear to be expensive and thus not affordable by most mothers [43]. Other studies carried out in poor resource settings of Vietnam and Nigeria also found a higher likelihood of U5M from mothers with transportation di culties [41,44]. However, the results between the previous studies and the current study should be translated cautiously due to time differences.…”
Section: Discussionmentioning
confidence: 54%
“…Nine were from Africa: Nigeria [40,41], Uganda [42], Malawi [43], Egypt [44], Ghana [45], Tanzania [46], Ethiopia [47] and Burkina Faso [48]. Nine were from Asia: China [49], India [50,51], Iran [52], Vietnam [53,54], Indonesia [55] and Pakistan [56,57].…”
Section: Resultsmentioning
confidence: 99%